A novel RyR1-selective inhibitor prevents and rescues sudden death in mouse models of malignant hyperthermia and heat stroke - Toshiko Yamazawa (Nature Portfolio, 2021)
Mutations in ryanodine receptor 1 (RyR1), a Ca2+ release channel in skeletal muscle, cause malignant hyperthermia (MH) and are involved in heat stroke. Here, the authors show that an oxolinic acid-derivative RyR1 inhibitor effectively prevents and treats MH and heat stroke in various MH mouse models.